2020
DOI: 10.1177/2292550320933687
|View full text |Cite
|
Sign up to set email alerts
|

Prepectoral Implant-Based Breast Reconstruction Using Meshed ADM

Abstract: Prepectoral prosthetic breast reconstruction has been widely reassessed in recent years and is taking on an increasingly important role in the field of immediate breast reconstruction. We report here a case series of 32 patients who underwent nipple-sparing mastectomy for breast carcinoma and prepectoral breast reconstruction involving an acellular dermal matrix (ADM) treated by means of a skin-graft mesher in our hospital from January 2015 to March 2016. The indications for this type of reconstruction were bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…Studies currently available on PPBR and fenestrated ADMs seem to confirm this hypothesis. Compared with 2.1% CC incidences reported in the iBAG study ( 53 ) and the weighted mean of 2.06% in this study, which is calculated with the Braxon® continuous collagen sheet, fenestrated-ADM-assisted PPBRs outline higher CC incidences: out of 71 breasts, Scheflan et al found an incidence rate of 8.5% of CC ( 119 ), while in the same year, Fin et al recorded 6% ( 120 ). More recently, Wazir et al reported a 12.5% incidence rate ( 121 ).…”
Section: Discussioncontrasting
confidence: 60%
“…Studies currently available on PPBR and fenestrated ADMs seem to confirm this hypothesis. Compared with 2.1% CC incidences reported in the iBAG study ( 53 ) and the weighted mean of 2.06% in this study, which is calculated with the Braxon® continuous collagen sheet, fenestrated-ADM-assisted PPBRs outline higher CC incidences: out of 71 breasts, Scheflan et al found an incidence rate of 8.5% of CC ( 119 ), while in the same year, Fin et al recorded 6% ( 120 ). More recently, Wazir et al reported a 12.5% incidence rate ( 121 ).…”
Section: Discussioncontrasting
confidence: 60%
“…Mean/median age ranged from 34.2 years 13 to 56.4 years. 14 Average follow-up was reported from 12 months 15 to 5 years. 16 The main study characteristics are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four different reviewers performed title and abstract review. Full-text review was conducted for 355 articles; 33 studies were eligible and underwent data extraction 16,17,29–62 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%